2018
DOI: 10.1093/pubmed/fdy188
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and change in sports activity among middle-aged and older men and women: evidence from the German Ageing Survey

Abstract: Background Sports activity (SA) behavior is unequally distributed across socioeconomic status (SES) groups. However, little is known about the impact of SES on change in SA over time. Methods Based on data from the German Ageing Survey, we examined the role of objective (education, occupational prestige, household equivalent income, composite SES-index) and subjective (self-rated standard of living) SES indicators on negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…“ Since previous studies indicate that the effect of SES on change in PA may differ by gender (…) we conducted all analyses for men and women separately .” ( 57 ) (p. 3).…”
Section: Resultsmentioning
confidence: 99%
“…“ Since previous studies indicate that the effect of SES on change in PA may differ by gender (…) we conducted all analyses for men and women separately .” ( 57 ) (p. 3).…”
Section: Resultsmentioning
confidence: 99%
“…SA was assessed using a single item ‘How often do you do sports, such as hiking, soccer, gymnastics, or swimming?’, and responses ranged from daily [ 1 ] to never [ 6 ] [ 33 ]. In line with previous studies [ 34 , 35 ], a dichotomized variable was created to differentiate between individuals who were active (response options ‘daily’, ‘several times a week’ and ‘once a week’) or inactive (response options ‘between 1 to 3 times a month’, ‘less often’ and ‘never’). Based on the SA levels at the follow-up assessment, four patterns of SA change were identified: (i) People who were physically inactive at baseline and follow-up assessment (remained inactive), (ii) persons who changed their SA from active at baseline to inactive at follow-up assessment (became inactive), (iii) persons who were active at baseline and follow-up assessment (remained active), (iv) persons who changed their SA from inactive at baseline to active at follow-up assessment (become active).…”
Section: Methodsmentioning
confidence: 99%
“…Gender, time since retirement, and the number of physical diseases from a list of 12 (cardiovascular disease, peripheral vascular disease, back pain, asthma and other respiratory diseases, gut diseases, malignant neoplasms, diabetes, liver or kidney diseases, incontinence, sleep disturbances, visual problems, hearing loss) at follow-up were entered as potential confounders. Previous studies show that changes in PA during the retirement transition differ between men and women [ 15 , 19 , 29 , 34 ], and that health restrictions influence participation in PA [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown a global decrease in physical activity and sport participation among children and adolescents in western countries. [8][9][10][11][12][47][48][49] In France, national 17 studies show a stability in adolescents' sport participation rates. Locally, a regional study shows a 15-points decline between 2001 and 2015.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%